An Acute Permethrin Exposure Causes Significant Microbial Shifts in Montastraea cavernosa - MacKnight, Nicholas J.; Arick, Lindsay; Crawford, Amelia C.; Henry, Michael; Pierce, Richard; Muller, Erinn M. (Frontiers in Marine Science, 2022)
Insecticide use is common in developed tropical regions where it may enter coastal reef ecosystems through land-based sources. This local introduction of contaminants could affect ecosystem health as corals can better withstand global stressors more readily if local pressures are reduced. The present study investigated the microbial community and photochemical efficiency of the reef building coral, Montastraea cavernosa, when exposed to the commercially applied insecticide, permethrin. Montastraea cavernosa was exposed to an acute concentration of permethrin for 24 h in a controlled laboratory setting. Fourteen fragments were integrated across four treatments (2 or 0.325 μg/l of permethrin, acetone control, and saltwater control) with three to four replicates per treatment. Photosynthetic efficiency was measured by quantifying the maximum photochemical yield and maximum electron transport rate (ETR), which were recorded for each fragment before exposure and 24 h after exposure to permethrin. The microbial communities of M. cavernosa tissue was measured using 16S rRNA sequencing for each fragment. Permethrin exposure at the tested concentrations suggested no significant effect on the M. cavernosa’s photochemical parameters measured during the 24-h permethrin exposure. Microbial communities were significantly different between permethrin treated (2 and 0.325 μg/l) and non-treated conditions (acetone and saltwater controls). In permethrin treated coral, this study documented a significant increase in Burkholderia pyroccinnia and Bacillus sp., bacteria groups known to bioremediate insecticides. Exposure of permethrin also decreased the relative abundance of Mesorhizobium sp., Sediminibacterium sp., Sphingorhabdus sp., and Chondromyces sp., which are known to inhibit pathogen colonization and provide essential macromolecules. Therefore, although the symbiotic relationship between the host and the intracellular algae remained intact after the corals were exposed to permethrin, the significant shift in the microbiome indicate permethrin may destabilize the microbial composition of the holobiont.